Thoughts on the Biological Evaluation of Biodegradable Cardiovascular Implants - Yun XU; Maobo CHENG; Peng ZHAO (Zhongguo yiliao qixie zazhi)
In recent years, new degradable materials have been applied to cardiovascular implants. Cardiovascular implants with different physicochemical properties and degradation properties have special endpoints for their biological evaluation. In this study, the end points of biological evaluation of degradable cardiovascular implants were reviewed by taking vascular stents and occluders as examples.